Problems of Finding Two or More Numbers from their Sum (Or Difference) and Multiple Ratios - Mukhammedovna, Kosimova Mavluda (International Journal of Human Computing Studies, 2022)
This paper analyzes examples of complex arithmetic tasks, problems of finding two or more numbers of the same type of typical arithmetic tasks from their sum (or difference) and multiple ratios.